Sub-chronic administration of brewed coffee on rat behavior and cognition and oxidative stress Alzheimer's disease model. (December 2019) - Sedaghat, Gohar; Mirshekar, Mohammad Ali; Amirpour, Mahsa; Montazerifar, Farzaneh; Miri, Somayeh; Shourestani, Shadi
Summary: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by intracellular neurofibrillary tangles and neuro-inflammation. Growing experimental evidence indicate diverse biological effects of brewed coffee (BC) including antioxidant, neuroprotective and anti-inflammatory. However, the underlying neuroprotective mechanism of BC is still largely elusive. Keeping this in mind, the present study was aimed to investigate the neuroprotective effects of BC on STZ-induced AD. We observed that path length and latency time and path length increased in STZ induced AD while BC administration enhanced these indices in the BC-STZ group. After treatment with BC, latency times in groups with memory impairment enhanced in shuttle box and MWM tasks. Biochemical factors including lipid peroxidation marker and tumor necrosis factor-α increased in STZ induced AD and BC treatment ameliorated these. Total anti-oxidant concentration level has reduced in AD rats and otherwise, BC treatment has prevented its reduction. Our study demonstrated that BC pretreatment significantly improved spatial learning and memory functions, effectively mitigated ICV-STZ mediated neuronal oxidative stress and improved neurobehavioral functions. Moreover, BC attenuated hippocampal neuro-inflammatory response in the hippocampus. Thus, our study further provides evidence for the therapeutic supplementation of BC for various neurodegenerative disorders including AD.